2000
DOI: 10.1007/s004060070006
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent predictors of schizophrenia in the Northern Finland 1966 Birth Cohort – a descriptive life-span model

Abstract: Subtle motor, emotional, cognitive and behavioral abnormalities are often present in apparently healthy children and adolescents who later develop schizophrenia. This suggests that some aspects of causation are established long before psychosis is manifest. We aim to develop a descriptive model of the factors contributing to the development of schizophrenia. Our main focus is on genetic factors, pregnancy and delivery complications, early development and scholastic performance. This is done by reviewing the No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 78 publications
3
26
0
2
Order By: Relevance
“…19 A study involving 61 patients with schizophrenia onsets before 18 years of age, showed a rate of enuresis of 36%.20 This approximates the present study's enuresis rate of 17% (2 out of the 12). In the National Institute of Mental Health (NIMH) study there was no evidence of increased obstetric complications or environmental stress.…”
Section: Discussionsupporting
confidence: 67%
“…19 A study involving 61 patients with schizophrenia onsets before 18 years of age, showed a rate of enuresis of 36%.20 This approximates the present study's enuresis rate of 17% (2 out of the 12). In the National Institute of Mental Health (NIMH) study there was no evidence of increased obstetric complications or environmental stress.…”
Section: Discussionsupporting
confidence: 67%
“…6,20 It is well known that mental disorders in pregnant women may also alter the mother-fetus relationship and the future development of the child, which may be perceived in the newborn initially as excessive crying, irritability, or apathy, and may lead to affective disorders in adult age. [8][9][10] Multiprofessional care with pregnant women must encompass the interactions between a range of different factors. These include personal history, gynecological and obstetrical history, the timing of pregnancy within the woman's history, current social, cultural, and economic characteristics, and the quality of available care.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies of premorbid function have revealed abnormalities or developmental delays in neuromotor, cognitive, language, emotional or social functioning. (McNeil et al, 2000;Isohanni et al, 2000a;Jones, 2001;Fuller et al, 2002;Cannon et al, 2003). Jones et al (1994) studied the British 1946 birth cohort and found evidence of delayed motor and speech development by the age of 2 years in those children who developed schizophrenia as adults.…”
Section: Introductionmentioning
confidence: 99%